Network meta-analysis to evaluate the effectiveness of interventions to prevent falls in children under age 5 years. Issue 2 (25th July 2014) - Hubbard, Stephanie; Cooper, Nicola; Kendrick, Denise; Young, Ben; Wynn, Persephone M; He, Zhimin; Miller, Philip; Achana, Felix; Sutton, Alex
Abstract : Background: This study aimed to simultaneously evaluate the effectiveness of a range of interventions to increase the possession of safety equipment or behaviours to prevent falls in children under 5 years of age in the home. Methods: A recently published systematic review identified studies to be included in a network meta-analysis; an extension of pairwise meta-analysis that enables comparison of all evaluated interventions simultaneously, including comparisons not directly compared in individual studies. Results: 29 primary studies were identified, of which 16 were included in at least 1 of 4 network meta-analyses. For increasing possession of a fitted stair gate, the most intensive intervention (including education, low cost/free home safety equipment, home safety inspection and fitting) was the most likely to be the most effective, with an OR versus usual care of 7.80 (95% CrI 3.08 to 21.3). For reducing possession or use of a baby walker: education only was most likely to be most effective, with an OR versus usual care of 0.48 (95% CrI 0.31 to 0.84). Little difference was found between interventions for possession of window locks (most intensive intervention versus usual care OR=1.56 (95% CrI 0.02 to 89.8)) and for not leaving a child alone on a high surface (education vs usual care OR=0.89 (95% CrI 0.10 to 9.67)). There was insufficient evidence for network meta-analysis for possession and use of bath mats. Conclusions: These results will inform healthcare providers of the most effective components of interventions and can be used in cost-effectiveness analyses.